KEBERHASILAN PBNYULUHAN KESEHATAN GIGI MENGGUNAKAN MEDIA POSTER DAN MEDIA MODEL PADA SISWA SD NEGERI 6 KAWAN BANGLI TAHUN 2OI4 - Sang Ayu Komang Apriyani; Ni Nengah Sumerti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Dental promotive eforts is one form of dental education process that require media as props,-especially media that can be used in various places such as posters, models, ilustrated books and others. Dental health education should be provided from on early age, ages 8 until I I years is the age group that vulnerable to the occurrence of dental caries in permanent teeth, but the best way of learning a student varies, some learn by seeing, watching, studying with doing for the actual, or read something that someone else ias preseited.The purpose of this study was determine the description of the success rate of dental health outreach using media posters and media models on elementary school students grades III and IV SD Negeri 6 Kawan. The research method used desiriptive study. Samples obtained by the total population of 40 students in grade III and IV SD Negeri 6 Kawan Bangli.The result of this research before to dental health outreach throughout the responden hove level of knowledge is less than 60% with less criteria. After dental health outreach with media posters s success rate 20% of the responden with extention very well criteria, 80% of respondent with good criteria. After dentat health outreach with media models a success rate 50% of the responden with extention very well criteria, 50% of respondent with good criteria. The average success outreach with media models is 79,75 is higher than success autreach with media posters which only 71,75.The conclusion of this research is media model can make respondent more understanding outreach than media poster. I would highly recommend to health physical education teacher SD Negeri 6 Kawan Bangli through the program UKGS in order to use media models than media poster on dental health outreach.